ENVIRONMENT CONSERVATION-LEGAL ISSUES AND IMLICATIONS - Jaiswal, Ayush; Krishnani, Madhuri (International Journal of Research -GRANTHAALAYAH, 2015)
In the last few decades the large scale environmental degradation has caused global concern about the conservation and protection of life on the earth. In the recent past we are hearing about environmental legislation which is no different from the goal set out in our constitution. It has become imperative to bring major change as far the enforcement mechanism is concerned. There is no doubt that the technological inventions and progress has over powered nature, it has also resulted in the thoughtless exploitation of nature. If man is able to transform deserts into oasis he is also leaving behind deserts in the place of oasis.